The Analysis of Hepatopancreas Histologycal Damage in Neocallichirus karumba (Poore and Griffin) Shrimp Caused by Heavy Metal Pb Exposure in Madura Strait - Kristiani, Maria; Herawati, Endang Yuli; Yanuhar, Uun (The Journal of Experimental Life Science, 2016)
Madura strait known as the second busiest shipping lanes in Indonesia. Human activities on the environment can influence the marine ecosystem derived from the household, fishery processing and capture fisheries. It can pollute coastal environments, one of which is heavy metal exposure such as Cd, Hg, Ca, As and Pb. These metals are greatly impacting the life of sea biota. The objective of this research, therefore, is to examine the hepatopancreas damage rate of shrimp Neocallichirus karumba due to the exposure of heavy metal Pb in Madura Strait. Method of research is by analyzing Pb content in water, sediment and shrimp by taking sample from 3 different stations. Hepatopancreas damage is then analyzed with SEM-EDX. Result of research indicates that at Station A, Pb pollution in water is the biggest and counted for 0.25 ppm, while those in sediment and shrimp are 5.85 ppm and 1.24 ppm. At Station B, Pb pollution in water is 0.19 ppm, whereas that in sediment is 5.51 ppm, but that in shrimp is 1.04 ppm. At Station C, Pb pollution in water counts for 0.18 ppm, and in sediment, it stands for 5.5 ppm but 0.02 ppm for shrimp. Result of analysis against hepatopancreas damage is explained as follows. At Station A, vacuolization is 20 % and Pb content in organ is 0.520 ppm. At Station B, the parameters are 10% and 0.196ppm. At Station C, it includes 15% and 0.173ppm. Organ damage is straightforwardly related to Pb content in water and sediment. Shrimp age is quite influential to the percentage of organ damage.Keywords: Heavy metal Pb pollution, hepatopancreas organ damage, Madura Strait, N. karumba shrimp.